Three- and five-year follow-up of a combined inpatient-outpatient treatment of obese children and adolescents - Sibylle Adam and Joachim Westenhöfer and Birgit Rudolphi and Hanna-Kathrin Kraaibeek (International journal of pediatrics, 2013)
Aim. “The combined DAK therapy for obesity in children and adolescents” combines a 6-week inpatient with a 10.5-month outpatient treatment. The aim of the study is to evaluate whether the therapeutic achievements are maintained two and four years after intervention. Method. All subjects who had participated in the 12-month program in 2004/2005 were included in the follow-up study. Body weight, height, and physical fitness were assessed through direct measurements, behaviour, and quality of life by self-report questionnaires. Statistical analysis is based on an intention-to-treat analysis. Results. The response rate after three years was 63.4% and 42.2% after five years. Within three years, participants reduced their BMI-SDS significantly by 0.20 (SD 0.49) and by 0.15 (SD 0.51) within five years. Significant positive changes could be observed with respect to the participants eating behaviour. Similarly, the food intake, particularly the consumption of calorie-reduced beverages, increased significantly while that of nonrecommended foods decreased. Improvement was also seen in the subjective quality of life as well as several aspects of self-perception. Conclusion. Compared to baseline data, significant reduction of BMI-SDS and positive changes of health-related behaviours could be observed even three and five years after the start of the initial program.